Ethical issues among tertiary students / Junaida Ismail, Aishah Musa, and Mahadir Ladisma @ Awis - Ismail, Junaida; Musa, Aishah; Ladisma @ Awis, Mahadir (Universiti Teknologi MARA, Shah Alam, 2017)
Issues regarding ethics always arise among students in tertiary institutions. McShane and Glinow (2008) defined ethics as “the study of moral principles or values that determine whether actions are right or wrong and outcomes are good or bad”. This study seeks to find out regarding the issue of ethics among university students. A total of 226 respondents participated in this study by completing a 24-item questionnaire. In general, the purpose of this study is to investigate the ethical behaviours among the Diploma students in UiTM Kedah. This study will focus on three (3) factors of academic environment namely; violation of school regulations, academic cheating and computer ethics.